Peran Sebagai Vaksinator Dalam Percepatan Vaksinasi Covid-19 Di Pesantren Islamic Center Binbaz - Ery Fatmawati; Muliawati, Dyah; Nining Sulistyawati; Muhammad Nur Hasan; Tri Hardi MU (LPPM STIKES Madani, 2023)
The COVID-19 pandemic and its rapid spread require effort. Apart from implementing strict health protocols, another possible way to prevent the spread of this virus is to get vaccinated. The aim is to contribute to efforts to accelerate the COVID-19 vaccination. This activity targets students and employees at the Bin Baz Islamic Center Islamic Boarding School (ICBB). This COVID-19 vaccination activity used the mass vaccination method with the participation of students, teachers, lecturers, and employees, as well as families, at the Bin Baz Islamic Center Islamic Boarding School (ICBB). The activity was held on October 26, 2022, and it went off without a hitch, with a total of 1312 participants, or 81% of the target. Based on the results of the observations of the vaccination implementation, there were no vaccine participants who experienced side effects that required treatment. The conclusion from the implementation of this activity is that it provides easy access to the COVID-19 vaccine for students and employees in the ICBB environment.